1974
DOI: 10.1007/bf00154978
|View full text |Cite
|
Sign up to set email alerts
|

OSO-7 observations of solar x-rays in the energy range 10?100 keV

Abstract: The solar X-ray experiment on the satellite OSO-7 has provided extensive observations of hard and soft X-ray bursts. We give a general description of the hard X-ray data here, in parallel with the description of the soft X-ray data already published (Datlowe et al., 1974). The data for this study consist of 123 hard X-ray bursts which occurred between 10 October 1971 and 6 June 1972. We examine the behavior of a typical event in terms of its spectral and flux variations. For the whole data sample, we find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(69 citation statements)
references
References 19 publications
5
63
0
1
Order By: Relevance
“…The most important result of the over-the-limb burst characteristics is that the fraction of the bursts which have a non-thermal component is 2/3, exactly the same as found for the 122 X-ray bursts studied in Datlowe et al (1974b). What is more, of the eight.bursts with expected locations with 0 greater than 1000, corresponding to minimum visible heights 4 5 from 10 to 10 km, five exhibit a detectable non-thermal component.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The most important result of the over-the-limb burst characteristics is that the fraction of the bursts which have a non-thermal component is 2/3, exactly the same as found for the 122 X-ray bursts studied in Datlowe et al (1974b). What is more, of the eight.bursts with expected locations with 0 greater than 1000, corresponding to minimum visible heights 4 5 from 10 to 10 km, five exhibit a detectable non-thermal component.…”
Section: Discussionsupporting
confidence: 67%
“…The height above which X-ray emission is observed can be expressed as In addition to those events, we have selected a set of 37 non-thermal 'limb' bursts identified from SGD as coming from flares located between 600 < 0 <900. As a reference for comparison to these, we used the same-set of 59 non-thermal events at 0O 0 <600 as used in Datlowe et al (1974b), hereafter identified as 'center' events.…”
Section: Data Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations show that the distribution of solar flare hard X-ray bursts is a power law in peak photon flux with logarithmic slope near 1.8 (Datlowe et al 1974;Dennis 1985;Lin et al 1984;Einaudi & Velli 1999;Charbonneau et al 2001). The powerlaw index of the distribution is independent of solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The results are power-laws, f (E) ∼ E −α , distributions with indexes α around 1.8 (Datlowe et al, 1974;Lin et al, 1984;Dennis, 1985;Crosby et al, 1993Crosby et al, , 1998Aschwanden et al, 2001). The later authors also present a substantial investigation of the total energy in the flare electrons observed in hard X-Ray bremsstrahlung, finding α = 1.5 ± 0.02.…”
Section: Introductionmentioning
confidence: 90%